Microservice-Based Platform for Space Situational Awareness Data Analytics - Wanjie Lu; Qing Xu; Chaozhen Lan; Liang Lyu; Yang Zhou; Qunshan Shi; Yinghao Zhao (International Journal of Aerospace Engineering)
The development, deployment, and maintenance of the current space situational awareness (SSA) information system have become increasingly complex. However, researchers cannot flexibly and conveniently apply the research results to practical applications due to the lack of basic research platforms for SSA. Inspired by X as a Service (XaaS), we propose the microservice-based platform for SSA data analytics to provide a scaffold-like platform for researchers. Based on microservice, the architecture for this platform is proposed to meet the requirements of flexible development and loosely coupled deployment. To facilitate the use of the platform, the hybrid data service layer is established to provide basic data for research and the functional service layer is designed to provide services for clients and applications. Due to the massive data processing requirements, the data analysis architecture and processing model, which can easily integrate various user-defined algorithms and significantly improve the computational efficiency, are proposed based on the Lambda architecture. To verify the platform’s effectiveness, two cases are established and implemented. The results show that this platform can provide a convenient, flexible, and efficient platform for the requirements of algorithm integration, experiment, and data display from users and researchers.